Radiological findings of soft tissue calcification in mandible through panoramic radiography: a literature review - Bima, Lukman; Abdul Rahman, Fadhlil Ulum (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: This review aims to analyze the role of digital panoramic radiography in identifying soft tissue calcifications in the mandibular region, summarize the prevalence and distribution of these calcifications based on recent literature (2018–2023), and critically evaluate the diagnostic necessity and relevance of complementary imaging modalities (CBCT, CT, MRI, and ultrasonography) for definitive characterization in each specific type of calcification. Review: Soft tissue calcifications in the maxillofacial region are frequently detected as incidental findings on panoramic radiographs performed for routine dental evaluations. Although panoramic radiography is not the first-line modality for soft tissue assessment due to the superimposition of anatomical structures and reduced contrast resolution, its wide coverage enables visualization of a variety of calcified entities. Based on the reviewed studies, the most frequently detected calcifications include sialoliths, carotid artery calcifications, tonsilloliths, stylohyoid ligament calcification, phleboliths, and calcified lymph nodes. Prevalence varies widely between populations (5.4–46.9%) and increases significantly with age, particularly in individuals over 40 years old. Gender association remains inconsistent across studies. Panoramic radiography demonstrates value in identifying potentially clinically significant findings, such as carotid artery atheroma, which may indicate increased systemic vascular risk. However, localization and characterization accuracy remain limited, and advanced imaging modalities such as CBCT and MRI demonstrate superior capability in differentiating tissue origin and defining lesion morphology. Conclusion: The most common soft tissue calcifications include sialoliths in the ramus or angle of the mandible, followed by calcifications of the carotid artery, stylohyoid ligament, phleboliths, tonsilloliths, and antroliths. The highest distribution is observed in the submandibular gland, followed by the parotid gland. Soft tissue calcifications are more prevalent in the middle-aged population, followed by young adults, and are more frequently found in women.